2010
DOI: 10.1371/journal.pone.0012632
|View full text |Cite
|
Sign up to set email alerts
|

CRY2 Is Associated with Rapid Cycling in Bipolar Disorder Patients

Abstract: BackgroundBipolar disorder patients often display abnormalities in circadian rhythm, and they are sensitive to irregular diurnal rhythms. CRY2 participates in the core clock that generates circadian rhythms. CRY2 mRNA expression in blood mononuclear cells was recently shown to display a marked diurnal variation and to respond to total sleep deprivation in healthy human volunteers. It was also shown that bipolar patients in a depressive state had lower CRY2 mRNA levels, nonresponsive to total sleep deprivation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 51 publications
3
42
0
Order By: Relevance
“…In addition, currently, there are no published data from Cry2 mutant mice on tests that induce anxiety-like or depressive-like behaviors, or on their alcohol intake. As such, this finding supports the view that CRY2 is clearly a "mood gene", since it is associated with a range of depressive phenotypes, including winter depression, on the basis of major depressive disorder (Lavebratt, Sjöholm, Soronen, et al, 2010), bipolar disorder (Sjöholm, Backlund, et al, 2010), the depressive episode of bipolar disorder (Lavebratt, Sjöholm, Soronen, et al, 2010), a chronic course of depressive symptoms due to major depressive disorder or bipolar disorder (Fiedorowicz, Coryell, Akhter, & Ellingrod, 2012), and dysthymia that is chronic depression (Kovanen, Kaunisto, Donner, Saarikoski, & Partonen, 2013).…”
Section: Anxiety Disorderssupporting
confidence: 79%
See 2 more Smart Citations
“…In addition, currently, there are no published data from Cry2 mutant mice on tests that induce anxiety-like or depressive-like behaviors, or on their alcohol intake. As such, this finding supports the view that CRY2 is clearly a "mood gene", since it is associated with a range of depressive phenotypes, including winter depression, on the basis of major depressive disorder (Lavebratt, Sjöholm, Soronen, et al, 2010), bipolar disorder (Sjöholm, Backlund, et al, 2010), the depressive episode of bipolar disorder (Lavebratt, Sjöholm, Soronen, et al, 2010), a chronic course of depressive symptoms due to major depressive disorder or bipolar disorder (Fiedorowicz, Coryell, Akhter, & Ellingrod, 2012), and dysthymia that is chronic depression (Kovanen, Kaunisto, Donner, Saarikoski, & Partonen, 2013).…”
Section: Anxiety Disorderssupporting
confidence: 79%
“…Mansour et al (2009) found no association with bipolar disorder in their further analysis of 252 SNPs of 18 genes in 523 patients with bipolar type 1 disorder and 477 controls, but NPAS2 rs17025005 and CRY2 rs1554338 suggested nominal associations with bipolar type 1 disorder. Further, the hypothesis-driven study by Sjöholm, Backlund, et al (2010) tested whether the 4 SNPs of CRY2 that had been associated with winter depression using samples of 204 patients and 2107 controls from two independent population-based studies (Lavebratt, Sjöholm, Soronen, et al, 2010) are associated with bipolar disorder. In a sample of 712 patients with bipolar disorder and 1044 controls, two risk haplotypes and one protective haplotype in CRY2 were identified for bipolar disorder with the feature of rapid cycling (Sjöholm, Backlund, et al, 2010).…”
Section: Bipolar Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Nr1d1 profile was found to be advanced during mania, when the amplitude of the gene expression profile was found higher compared to depression [23]. Moreover, the transcription of Chryptochrome 2, which has recently been found associated with bipolar rapid cycling disorder [96], was shown to be reduced in bipolar depressed patients compared to healthy controls.…”
Section: Circadian Gene Expressionmentioning
confidence: 77%
“…It has been associated with rapid cyclers (Sjoholm, Backlund et al 2010). More recently, a variant in CRY1 (rs8192440) was nominally associated with good treatment response to lithium (McCarthy, Nievergelt et al 2011).…”
Section: Clock Genesmentioning
confidence: 99%